Sistem Informasi Harga Komoditas Pangan untuk Pasar-Pasar di Kota Padang - Indri Rahmayuni; Yance Sonatha; Alde Alanda; Aldo Erianda (SOTVI - Society of Visual Informatics, 2020)
Padang City as the Capital of West Sumatra Province is the main gate of various types of trade commodities in the country. Padang is also a trading center in West Sumatra. Based on BPS data in 2016, there are 17 markets in Padang City with 8 markets managed by the community and 9 markets managed by the City Government of Padang. To assist the community in providing information on the prices of food commodities, a web-based information system is needed that provides information on the price of food commodities (especially basic food) for markets in the city of Padang. Through this information system, the public can find out the price of food commodities by grouping: per-commodity, per-market, and prices at a certain time period. The information system in the form of this website was created using the Laravel 5.5 framework which is one of the breakthroughs in the field of web programming. The Laravel Framework makes it easy for application developers to create web-based information systems. This information system is developed using the Waterfall method where development begins with the analysis, design, implementation, and testing stages.